Anaphylaxis in adolescents: a potential tripartite management framework. Issue 4 (August 2015) - Nwaru, Bright I.; Sheikh, Aziz
Abstract : Purpose of review: The incidence of anaphylaxis is increasing across all ages, but the risk of morbidity and fatality is disproportionately high in adolescents. This may, at least in part, be a consequence of a constellation of potentially modifiable psychosocial factors that tend to manifest during adolescence. This study highlights the shortcomings in and the barriers to effective management of anaphylaxis in adolescents, and proposes an integrated tripartite framework that may help promote successful management. Recent findings: Existing mainstay anaphylaxis self-management approaches – comprising careful avoidance of triggers, recognition of early features indicative of anaphylaxis and prompt self-administration of intra-muscular adrenaline (epinephrine) – often fail in adolescents. Key barriers to successful management centre on the impact of the psychosocial environment during adolescents' developmental transition. As a result, risk-taking, poor judgement of actions during reactions and non-compliance to management instructions are common. Summary: To be successful, anaphylaxis management strategies require more multidimensional approaches among adolescents. We propose a tripartite management framework that emphasizes integration of the following components: better understanding of adolescence; incorporation of the constituents of adolescents' social networks; and adolescent-tailored healthcare perspectives. This theoretical framework now requires translation into an intervention, feasibility and pilot testing, and formal evaluation through randomized controlled trials.